2009
DOI: 10.1021/np900515b
|View full text |Cite
|
Sign up to set email alerts
|

Revised Structure of the Alkaloid Drymaritin

Abstract: In 2004, a new anti-HIV alkaloid named drymaritin was isolated from Drymaria diandra. The authors identified the alkaloid as 5-methoxycanthin-4-one on the basis of spectroscopic data. Here we describe a synthetic approach that unambiguously gave 5-methoxycanthin-4-one, but the synthetic product showed spectroscopic data significantly different from those of the Drymaria alkaloid. Extensive re-evaluation of the spectroscopic data published for this and related alkaloids has led to the conclusion that drymaritin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
(15 reference statements)
3
28
0
Order By: Relevance
“…We agree with the authors, 28 theoretically be avoided. This example also convincingly shows that 13 C chemical shift calculation and dereplication of any isolated natural product are very useful as the first steps towards structure identification.…”
Section: 15supporting
confidence: 88%
See 3 more Smart Citations
“…We agree with the authors, 28 theoretically be avoided. This example also convincingly shows that 13 C chemical shift calculation and dereplication of any isolated natural product are very useful as the first steps towards structure identification.…”
Section: 15supporting
confidence: 88%
“…In this case, no chemical synthesis would be necessary to disprove structure 12.14. Structure 12.14, which was synthesized by Wetzel et al, 28 was also confirmed by strict structure generation (no NSCs) from the 2D NMR data 28 with the following results: k ¼ 4083-3874-1439, t g ¼ 12 min 6 s. The first ranked structure coincided with structure 12.14.…”
Section: 15mentioning
confidence: 56%
See 2 more Smart Citations
“…1). 2 Based on our long-term interest in canthin-6 -one, this reassignment drew our attention. Herein, we synthesized cordatanine unambiguously by a four-step procedure to validate the exact structure.…”
Section: Introductionmentioning
confidence: 99%